Islamic Educational Values in the Prevention and Mitigation of Stunting in Subulussalam City - Marwan Z; Habiburrahim; Sri Suyanta; Silahuddin (Pascasarjana Universitas KH. Abdul Chalim, 2026)
This study examines the role of Islamic educational values in the prevention and mitigation of stunting in Subulussalam City, Aceh. The urgency of this study is driven by the high stunting prevalence of 47%, which prompted the local government to conduct integrated interventions through various institutions such as the Health Office, Education Office, and the Ministry of Religious Affairs. Considering that Aceh is an Islamic region with a Muslim majority, a religious-based approach is seen as highly relevant in influencing community behavior. The objective of this study is to describe how Islamic educational values—worship (ibadah), faith (iman), and morals (akhlaq)—are integrated into stunting prevention programs. This research employs a qualitative case-study design using observation, interviews, and documentation as data collection techniques. Data were analyzed using descriptive qualitative analysis involving data reduction, data display, and conclusion drawing. The findings indicate that Islamic educational values are implemented by Islamic religious teachers, religious counselors, and health workers through education, counseling, premarital guidance, and community socialization activities. These values are integrated with Qur’anic verses and hadith related to family responsibility, breastfeeding, and nutritional fulfillment. This approach enhances community knowledge, encourages behavioral change toward a healthy lifestyle, and reinforces the belief that maintaining children’s health is a religious duty. The study concludes that integrating Islamic educational values into public health programs can serve as an effective strategy for stunting prevention, especially in religious-based communities. The implication of this research suggests that policy synergy between religious institutions and health agencies can strengthen the sustainability of stunting reduction programs.